Strengths and weaknesses of meat inspection as a contribution to animal health and welfare surveillance - Stärk, K.D.C.; Alonso, Silvia; Dadios, N.; Dupuy, C.; Ellerbroek, L.; Georgiev, M.; Hardstaff, J.; Huneau-Salaun, A.; Laugier, C.; Mateus, A.; Nigsch, A.; Afonso, A.; et al. (Elsevier, 2014)
Meat inspection (MI) is one of the most widely implemented and longest running systems of surveillance. It was primarily introduced to identify meat of animals that is not fit for human consumption. Additionally, MI was progressively recognised as a suitable source of data collection and for monitoring a broad spectrum of diseases and conditions concerning animal health and welfare. For Europe, MI tasks are regulated at the European rather than country level and include a set of activities before and after stunning (ante and post mortem inspection) involving visual inspection, palpation and incisions. Over the last decade, the current MI protocol has been challenged because of its low sensitivity for important public health hazards. We aimed to assess the strengths and weaknesses of current MI protocols with primary focus on its utility in the context of animal health – including both notifiable and production diseases – and welfare, i.e. its capacity to detect cases with an aim to quantify the frequency of animal disease and welfare cases. The consequences of an alternative inspection protocol using visual-only inspection were also explored. As a first step, a review of grey and published literature was conducted for a selected number of diseases and welfare conditions in seven species or species groups: swine, poultry, bovines, small ruminants, solipeds and farmed game, represented by red deer, wild boar, rabbits and ostriches. This review highlighted a substantial lack of suitable and accessible published data on the frequency of occurrence of many diseases and conditions affecting food animals in Europe. Additionally, there were very limited data on the detection performance of MI, particularly in relation to specific degrees of severity of clinical signs. Due to the data gaps, a large proportion of input data used in this work was based on expert opinion and general biologic manifestations of the conditions investigated. The probability of case detection was quantified using a scenario tree modelling approach, taking into account the frequency of case presentation and inspection coverage. In general, the performance of MI was highly correlated with the presence of clinical and/or pathological signs in affected animals. Early or subclinical cases were likely to be “non-detectable” at slaughter. Regarding detectable cases, the impact of moving to visual-only inspection was negligible for most notifiable diseases and conditions considered with a few exceptions, primarily detectable cases of tuberculosis. Current MI activities were found to be effective to detect the majority of animal welfare conditions considered by species, predominantly by ante mortem inspection. The effectiveness of MI was also considered for endemic diseases that are not currently subject to systematic control efforts. These included respiratory diseases and parasite infections. It was shown that MI could provide an efficient means of identifying producers in need of animal health advice, provided that information is collected and fed back to veterinarians and livestock farmers. Within an integrated information system, MI could substantially contribute to the control of a considerable range of animal health and welfare issues. Data already collected need to be made available for on-farm decision making. It was also noted that if the slaughter population is strongly affected by international trade, i.e. where a large proportion of animals originate from one country and are slaughtered in another, the usefulness of MI for endemic disease surveillance will be affected by either reduced coverage or bias or both. In conclusion, our results indicate that while ante mortem inspection remains essential for the detection of animal welfare conditions, a move to visual-only post mortem inspection has - for the diseases and conditions considered - negligible negative impact on disease control. However in countries or regions that are not free of TB, special relevance of palpation and cutting of lymph nodes will have to be considered. MI information has considerable potential to inform disease control efforts, but only few countries use it systematically limiting the actual benefit that is achieved by these data. Finally, MI can also provide “back-up” surveillance in a situation where other means of detection fail and may represent the sole means of case detection for certain infections (e.g. liver fluke or cestodes).